REKAYASA MEDIA TANAM MENGGUNAKAN TONGKOL JAGUNG DAN DEDAK TERHADAP PERTUMBUHAN DAN PRODUKSI JAMUR TIRAM (Pleurotus ostreatus) - Kartika Oktasari; Husain Syam; Jamaluddin P Jamaluddin P (Jurnal Pendidikan Teknologi Pertanian, 2015)
The cultivation of oyster mushroom (Pleorotus ostreatus) is not many expanded yet in Indonesia, either the exertion chance or the consumtion fulfillment of society. The objective research is to know the growt, production, storability, and the protein content  degree of oyster mushroom on the basic media of sawdust were mixed with some compositions of corn cob flour brand. The research was arranged on completely random design with treatments mixture of sawdust from jati wood with corn cob (15%,25%,35%) and brand (15%,25%,35%). Oyster mushroom growth were observed at seven days after inoculation. The data were analyzed by of Varian Analysis (ANOVA) and continued with Duncant Multiple Range Test (DMRT) on 5% level.Result showed that corn cob and brand were effective admixture to enhance oyster mushroom production. The optimal growth, production, and protein content is  found in the mixture of brand media with concentration 35% , while for corn cob  media with concentration 25% But for the storability of oyster mushroom the result showed that the corn cob and brand has not a significant influence